Classical Hodgkin’s Lymphoma Presenting as Erythroderma - Kumar Parimalam; R Priyavathani; Kannan Rajkumar; Rajan Manipriya; Elangovan Supriya (Journal of Clinical and Diagnostic Research, 2022)
Hodgkin’s Lymphoma (HL) with direct cutaneous involvement is uncommon, unlike non specific paraneoplastic skin changes, which can occur during the course of the disease. Direct cutaneous infiltration commonly affects the chest and manifests as papules and plaques. Nodules in some patients may ulcerate. Paraneoplastic manifestations can be eczematous itchy papules or lichenified plaques adjacent to the affected lymph nodes. Authors’ reported a case of a 31-year-old female with erythroderma, of four months duration, who did not respond to treatment with corticosteroids and cyclosporine. Skin biopsy showed minimal epidermotropism without mitotic cells. Immunohistochemistry (IHC) showed CD3, CD4, CD5 and CD8 positivity and CD15, CD 20 negativity. She had frequent exacerbations while on treatment with steroids. Amongst this confusing clinical picture, it was the emergence of an axillary lymph node, after two months of initiating treatment which on histopathology was compatible with HL and on IHC positive for CD3, CD20 and CD30 and negative for CD15. These findings confirmed the diagnosis as classical HL. The present case is being reported to highlight the importance of thorough clinical examination with particular reference to lymph node screening.